Strategies for enhancing yellow book literacy through the al-miftah lil ‘ulum method: A quantitative study at miftahul huda islamic boarding school - Hamid Syarifuddin; Sukari (At Turots: Jurnal Pendidikan Islam, 2025)
This research examines the effectiveness of the Al-Miftah lil ‘Ulum method as a strategy for improving reading literacy skills regarding yellow books among the students of Miftahul Huda Islamic Boarding School located in Kalijambe, Sragen. The research question posed is: What is the impact of implementing the Al-Miftah lil ‘Ulum method on the enhancement of yellow book literacy among the students? This study employs a quantitative approach, utilizing structured questionnaires distributed to 20 students participating in the program for data collection. Descriptive statistical analysis is applied to interpret the data, focusing on frequency distribution and percentages. The findings indicate that the implementation of the Al-Miftah lil ‘Ulum method significantly enhances the students' ability to master the fundamentals of Nahwu and Sharf, independently translate Arabic sentences, and expand their vocabulary comprehension. Additionally, this method fosters increased motivation and engagement among the students in the study of yellow books. These findings underscore the considerable potential of structured methodological interventions in strengthening the literacy of classical texts within Islamic educational institutions. This study recommends the adoption of structured methods such as Al-Miftah lil ‘Ulum to improve literacy competencies within the pesantren environment.